Adaptive half-metallicity via magnetic proximity in an electrically sensitive 1T'-WTe₂/CrBr₃ vdW heterostructure - Bora, Mayuri (2023)
The magnetic proximity effect (MPE) together with electric-field tunability en-routes new physical paradigm in developing nanoscale devices by modulating the functionalities of the materials. By employing first-principles calculation, we investigate MPE in a van der Waals (vdW) heterostructure constituted by a monolayer Weyl semimetal 1T’-WTe2 (tungsten di-telluride), coupled with a monolayer ferromagnet CrBr3 (chromium tribromide) at an interplanar distance of 3.68 Å. The proximity effect infers that the heterostructure system is 100 % spin-polarized leading to half-metallic nature, with a spin-splitting of 25 and 10 meV for two spin configurations. This robustness of MPE arises due to orbital hybridization and charge transfer at the interface of heterostructure system. Moreover, half-metallic nature is tuned and transformed to semiconducting and overlapping states in presence of external bias. The spin-splitting manifests orbital hybridization due to d-orbitals of W and Cr with a notable enhancement of 4 % in the magnetic moment value (12.04 µB per cell). We also observe that proximitized interface is highly sensitive towards an application of external electric field. With external bias, the Fermi level across charge neutrality point is easily tuned and controls charge transport at interface. The consistent nature of conductivity enables the interfacial polarization and coherent electron drift is realized due to seamless proximity interaction across the transport channel of the heterostructure system. This electric field-mediated MPE in vdW heterostructure can strongly recommend for next-generation spin filtering and field effect transistor (FET) devices.